Embryonic Stem Cell–Derived Exosomes Promote Endogenous Repair Mechanisms and Enhance Cardiac Function Following Myocardial Infarction. Issue 1 (19th June 2015) - Khan, Mohsin; Nickoloff, Emily; Abramova, Tatiana; Johnson, Jennifer; Verma, Suresh Kumar; Krishnamurthy, Prasanna; Mackie, Alexander Roy; Vaughan, Erin; Garikipati, Venkata Naga Srikanth; Benedict, Cynthia; Ramirez, Veronica; Lambers, Erin; et al.
Abstract : Rationale: : Embryonic stem cells (ESCs) hold great promise for cardiac regeneration but are susceptible to various concerns. Recently, salutary effects of stem cells have been connected to exosome secretion. ESCs have the ability to produce exosomes, however, their effect in the context of the heart is unknown. Objective: : Determine the effect of ESC-derived exosome for the repair of ischemic myocardium and whether c-kit + cardiac progenitor cells (CPCs) function can be enhanced with ESC exosomes. Methods and Results: : This study demonstrates that mouse ESC-derived exosomes (mES Ex) possess ability to augment function in infarcted hearts. mES Ex enhanced neovascularization, cardiomyocyte survival, and reduced fibrosis post infarction consistent with resurgence of cardiac proliferative response. Importantly, mES Ex augmented CPC survival, proliferation, and cardiac commitment concurrent with increased c-kit + CPCs in vivo 8 weeks after in vivo transfer along with formation of bonafide new cardiomyocytes in the ischemic heart. miRNA array revealed significant enrichment of miR290-295 cluster and particularly miR-294 in ESC exosomes. The underlying basis for the beneficial effect of mES Ex was tied to delivery of ESC specific miR-294 to CPCs promoting increased survival, cell cycle progression, and proliferation. Conclusions: : mES Ex provide a novel cell–free system that uses the immense regenerative power of ES cells while avoiding the risks associated with direct ES or ES-derived cell transplantation and risk of teratomas. ESC exosomes possess cardiac regeneration ability and modulate both cardiomyocyte and CPC-based repair programs in the heart. Abstract : Supplemental Digital Content is available in the text.